Integration basis of figural training of future architects (Pedagogy of Higher and Secondary Education, 2009)
The article discusses the integration aspects of fine art training of future architects, set directions and ways to integrate the learning process, outlined the main provisions of the technical system of integrated composite concepts.
Keywords: integration; visual training; composition